Pengaruh Penerapan Peran Komite Audit, Peran Dewan Pengawas Syariah dan Efektivitas Pengendalian Intern atas Pelaporan Keuangan terhadap Kualitas Pelaporan Keuangan - Rini Rini (Jurnal Akuntansi dan Keuangan Islam, 2014)
This study examines the effect of audit committee role, shari’a supervisory board role,and internal control over financial reporting effectiveness, on financial reporting quality.The data is taken by questionnaire from 173 employees (group head, division head, andinternal auditor), audit committee members, and shari’a supervisory board members of33 Islamic banking in Indonesian. Research results that used path analysis, show that apositive correlation exists between audit committee role, shari’a supervisory board role,and internal control over financial reporting effectiveness. There is strongest relationshipbetween shari’a supervisory board role with internal control over financial reportingeffectiveness. Furthermore, audit committee role, shari’a supervisory board role, andinternal control over financial reporting effectiveness influence financial reporting quality simultaneously. Partially audit committee role, and internal control over financialreporting effectiveness influence financial reporting quality, but statistically shari’a supervisory board role was not significant.